Engineering Activity and Engineering Thinking in the Context of Artificial Intelligence Expansion - V. S. Sheinbaum; V. S. Nikolskiy (Высшее образование в России)
The academic press is increasingly discussing the impact of Artificial Intelligence (AI) technologies on education and science. Researchers pay attention not only to the applied aspects of the use of AI technologies, but also to the issues of the ontological foundations of activity that are being transformed under the influence of new technologies. However, the issues of the impact of AI technologies on engineering activity, engineering thinking and, consequently, on engineering education are not sufficiently reflected in academic publications. Moreover, the aspects related to the widespread use of artificial intelligence, both in professional activities and in everyday life, remain insufficiently studied.The article proposes theses and corresponding arguments that clarify the fundamental changes occurring in engineering activity and engineering thinking in the context of the expansion of artificial intelligence technologies. Engineering activity is presented as a system that is not identical to the activity of individual engineers. A definition of engineering activity is proposed, which reveals its essence through its goal of solving human and societal problems. A non-instrumental approach to the interpretation of engineering based on AI technologies is substantiated, within which artificial intelligence appears as a partner in engineering activity. Finally, engineering thinking is complemented by anticipatory and responsible thinking.The article is a contribution to the academic discussion on the specifics of engineering activity and engineering thinking at the present stage.